(untitled) (Malaysian Management Journal, 1997)
In its steady advance toward Vision 2020, Malaysia has been working hard to balance the skills and competencies of its people commensurate with its economic growth. To this end, educational twinning programmes abound in Malaysia. At present, these programmes are inevitably reliant to a considerable degree on Western thought and science. This paper, written from the perspective of two twinning programme directors, examines cross-cultural management issues underlying educational programme design and delivery. Its focus concentrates on. the execution of commerce and business programmes. Twinning programmes in commerce and business in. Malaysia may be heralding a new era in management education—that of the global manager, capable of conducting business with sensitivity and efficiency across a number of cultures and ideologies, These programmes which operate at the confluence of global schools of thought, including Buddhist-Confucian-Taoist, Islamic, Judaeo-Christian and Vedic-Hindu, present significant pedagogical challenges. This paper discusses these challenges, including areas of cross-cultural difference requiring sensitivity and discretion, and resultant issues in course design and delivery. This paper concludes with a number of dilemmas for those involved in management education—dilemmas with potential long-term implications for both Malaysia and the Western nations that currently provide the curricula for twinning programmes.